2002
DOI: 10.1530/eje.0.1470287
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic mutations in the thyrotropin receptor of autonomously functioning thyroid nodules in the Japanese population

Abstract: Objective: Constitutively activating mutations of the thyrotropin receptor (TSHR) have been found in the majority of autonomously functioning thyroid nodules (AFTNs) in European patients. The reported frequency of these mutations varies among reports but amounts to 50 -80%. To date, only one such mutation responsible for AFTNs has been identified in the Japanese population and the pathogenic role of such mutations in Japanese AFTNs has been questioned. In the present study, we evaluated the frequency of activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…In Europe and Japan, one of the main mechanisms responsible for the hyperfunction and growth of thyroid autonomous adenomas is the constitutive activation of the cAMP-dependent mitogenic cascade, through mutations conferring constitutive activity of the TSH receptor (50-80%) or an activating mutation of G sa (8%) (Russo et al, 1995;Van Sande et al, 1995;Fuhrer et al, 1997;Tonacchera et al, 1999;Vanvooren et al, 2002). Similar mutations account for hyperfunctioning nodules in multinodular goiters (Tonacchera et al, 1999(Tonacchera et al, , 2000Krohn et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe and Japan, one of the main mechanisms responsible for the hyperfunction and growth of thyroid autonomous adenomas is the constitutive activation of the cAMP-dependent mitogenic cascade, through mutations conferring constitutive activity of the TSH receptor (50-80%) or an activating mutation of G sa (8%) (Russo et al, 1995;Van Sande et al, 1995;Fuhrer et al, 1997;Tonacchera et al, 1999;Vanvooren et al, 2002). Similar mutations account for hyperfunctioning nodules in multinodular goiters (Tonacchera et al, 1999(Tonacchera et al, , 2000Krohn et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, Kosugi et al analyzed the entire exon 10 of the TSHR gene and found the first activating mutation in the TSHR gene in a Japanese patient with AFTN [17]. Vanvooren et al consistently identified four mutations in the TSHR gene in 10 Japanese AFTN patients and thus suggested that activating mutations in the TSHR gene may not be rare in the Japanese population [18]. In contrast to the TSHR gene, the incidence of the mutations in Gsα is reportedly low in Europe as well as in Japan [18][19][20]22].…”
Section: Discussionmentioning
confidence: 99%
“…The polymerase chain reaction (PCR) was performed in a 25 µl reaction volume containing 100-200 ng of genomic DNA, 10 pmol of each upstream and downstream primer, 1.25 units of Taq polymerase (Takara, Otsu, Japan), 0.2 mM each dNTP, and 2 mM MgCl 2 . All the reactions were started by an initial denaturation at 95°C for 5 min (except for exon 9 of TSHR at 93°C for 2 min 30 sec and exon 10 of TSHR at 94°C for 2 min), followed by 35 cycles of denaturation at 94°C for 30 sec, annealing at 55°C for 30 sec (except for exon 9 of TSHR at 61°C for 30 sec) and extension at 72°C for 1 min [17,18,22]. Aliquots of PCR products were run in 1% agarose gel electrophoresis and visualized with ethidium bromide to verify their quality.…”
Section: Sequencing Of the Tshr And Gsα Genesmentioning
confidence: 99%
See 2 more Smart Citations